Hubungan Faktor Sosio Demografi terhadap Kepuasan Pengguna Layanan Disdukcapil Sebelum dan Saat Pandemi Covid-19 - Junariah Junariah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of this study was to analyze the relationship between the Socio-Demographic factors of the community and the satisfaction of Disdukcapil service users in Prabumulih City before and during the Covid-19 pandemic. The research method uses quantitative methods. The research sample is 100 respondents. Data collection techniques with documentation, questionnaires and observation. Data analysis with univariate and bivariate analysis. The results of the study obtained data that the service indicators before Covid-19 were Tangible, Reliability, Responsivenes, Assurance, the results of all service indicators were very satisfying, while the results of the service indicators during Covid-19 were Tangible and Empathy while the indicators of Reliability, Responsiveness and Assurance were satisfying. The services provided before Covid-19 were very satisfying, while the services during Covid-19 were satisfactory because there were unsatisfactory indicators. Based on the socio-demographic factors, namely age, gender, education and occupation, there is no significant effect between these variables and the satisfaction of Disdukcapil service users before and during the Covid-19 pandemic. The conclusions of the study show that the satisfaction of disdukcapil service users does not show a significant difference. Keywords: Covid-19 Pandemic, Service, Sociodemography